Aksi Sosial Mengajar Anak Taman Pendidikan Al-Qur’an Masjid Andalusia Islamic Center - Qolbi, Rahma ‘Aziza Lathifatul (Tazkia Islamic University College, 2024)
Research problems, gap analysis, objectives, methodology, discussion, finding. Andalusia The Andalusia Islamic Center Mosque is a result of profound creativity to address the challenges faced by Indonesia and its people. These challenges include backwardness in education, high levels of poverty, and low morality observed in various layers of society, both in the government and private sectors. Thus in the empowerment program of the teaching action for the years 2021-2023, it became the focus of activities to address unresolved issues. The objectives of this teaching action include: 1) Applying knowledge and skills by developing teaching abilities, 2) Developing the character and potential of children to become a Quranic generation, 3) Motivating children to study outside of their busy school schedule, 4) Providing teaching and learning experiences by interacting with children, 5) Making a tangible contribution to the community and the campus in terms of children's education, thereby improving the quality of education.